Media effects of protest movements in the context of nonlinear dynamic - D. A. Popov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article analyzes the factors and conditions for the emergence of political and social protest in modern political regimes, reveals the essence of the political maneuver of national governments and political manipulation in the political conditions of unstable external environment.